CRIMINAL LIABILITY FOR FRAUDULENT ENTREPRENEURSHIP (Web of Teachers: Inderscience Research, 2024)
This article examines the concept of "fake entrepreneurship" and its criminal liability under the law. It also examines the criminal aspects of fraud, including tax evasion, falsification of business activities, and illegal profit-making. It also outlines the forms of fake entrepreneurship, legal mechanisms for their detection, and penalties established by criminal law.